Transient Decrease in Circulatory Testosterone and Homocysteine Precedes the Development of Metabolic Syndrome Features in Fructose-Fed Sprague Dawley Rats - Anil Sakamuri; Sujatha Pitla; Uday Kumar Putcha; Sugeedha Jayapal; Sailaja Pothana; Sai Santosh Vadakattu; Nagabhushan Reddy Konapalli; Siva Sankara Vara Prasad Sakamuri; Ahamed Ibrahim (Journal of Nutrition and Metabolism)
Background. Increased fructose consumption is linked to the development of metabolic syndrome (MS). Here we investigated the time course of development of MS features in high-fructose-fed Sprague Dawley rats along with circulatory testosterone and homocysteine levels. Methods. Rats were divided into control and experimental groups and fed with diets containing 54.5% starch and fructose, respectively, for 4, 12, and 24 weeks. Plasma testosterone and homocysteine levels were measured along with insulin, glucose, and lipids. Body composition, insulin resistance, and hepatic lipids were measured. Results. Increase in hepatic triglyceride content was first observed in metabolic disturbance followed by hypertriglyceridemia and systemic insulin resistance in fructose-fed rats. Hepatic lipids were increased in time-dependent manner by fructose-feeding starting from 4 weeks, but circulatory triglyceride levels were increased after 12 weeks. Fasting insulin and Homeostatis Model Assessment of Insulin Resistance (HOMA-IR) were increased after 12 weeks of fructose-feeding. Decreased visceral adiposity, circulatory testosterone, and homocysteine levels were observed after 4 weeks of fructose-feeding, which were normalized at 12 and 24 weeks. Conclusions. We conclude that transient decrease in circulatory testosterone and homocysteine levels and increased hepatic triglyceride content are the earliest metabolic disturbances that preceded hypertriglyceridemia and insulin resistance in fructose-fed SD rats.